2022
DOI: 10.1371/journal.pone.0266893
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Epstein-Barr Virus (EBV) miRNA biomarkers for survival outcome in EBV-associated epithelial malignancies: Systematic review and meta-analysis

Abstract: Background The EBV-associated epithelial tumours consist 80% of all EBV-associated cancer, where the nasopharyngeal cancer (NPC) and EBV-associated gastric carcinoma (EBVaGC) are considered as the most frequent EBV-associated epithelial tumours. It has been shown that the BART-encoded miRNAs are abundantly expressed in EBV-associated epithelial tumours, hence, these miRNAs may serve as diagnostic and prognostic biomarkers for EBV-associated epithelial tumours. Therefore, the purpose of this systematic review a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 99 publications
(158 reference statements)
0
10
0
Order By: Relevance
“…Further, larger scale studies would be beneficial in understanding the various dimensions of EBVaGCs and their differences compared to EBVnGCs. Additionally, therapeutics targeting EBV-associated miRNAs are relatively unexplored ( 111 ) and given the roles for these virally encoded miRNAs in EBV-positive malignancies ( 100 ), could make for effective targets. An example of such a therapeutic was in a recent study in which researchers employed anti-miRNAs to silence miR-BART7-3p, reducing tumor growth in tested animal models ( 305 ).…”
Section: Perspectives and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, larger scale studies would be beneficial in understanding the various dimensions of EBVaGCs and their differences compared to EBVnGCs. Additionally, therapeutics targeting EBV-associated miRNAs are relatively unexplored ( 111 ) and given the roles for these virally encoded miRNAs in EBV-positive malignancies ( 100 ), could make for effective targets. An example of such a therapeutic was in a recent study in which researchers employed anti-miRNAs to silence miR-BART7-3p, reducing tumor growth in tested animal models ( 305 ).…”
Section: Perspectives and Discussionmentioning
confidence: 99%
“…Specifically, miR-BART5-5p and miR-BART19-5p are able to downregulate LMP1, an activator of many cellular immune signalling pathways ( 109 , 110 ). Upregulated expression of EBV miRNA is associated with a 3-times higher mortality risk in NPCs and GCs ( 111 ), with miR-BART20-5p specifically associated with worse recurrence-free survival in EBVaGCs ( 112 ).…”
Section: Role Of Ebv Mirnas In Ebvagc Tumor Progressionmentioning
confidence: 99%
“…A meta-analysis concluded that miRNA expression increased the mortality risk in NPC and GC patients by threefold (hazard ratio: 3.168; 95% CI: 2.020–4.969), meaning they may be used as prognostic biomarkers. Based on the survival data of 711 NPC and 59 GC patients, the meta-analysis investigated a total of seven EBV miRNAs, which were all upregulated [ 163 ]. A better understanding of EBV-miRNA expression in EBV-associated GC and NPC will open up new avenues for GC and NPC treatment [ 163 , 164 ].…”
Section: Sequencing Next-generation Sequencing and New Ebv Markersmentioning
confidence: 99%
“…Based on the survival data of 711 NPC and 59 GC patients, the meta-analysis investigated a total of seven EBV miRNAs, which were all upregulated [ 163 ]. A better understanding of EBV-miRNA expression in EBV-associated GC and NPC will open up new avenues for GC and NPC treatment [ 163 , 164 ]. Circular RNAs are another class of predominantly non-coding RNAs, which may play a role in the viral biology and pathogenicity of EBV-associated malignancies.…”
Section: Sequencing Next-generation Sequencing and New Ebv Markersmentioning
confidence: 99%
“…By regulating the immune landscape, miRNAs may directly and indirectly aid the infected host cell in malignant transformation. A recent meta-analysis evaluated the prognostic value of miRNAs in NPC and EBVaGC and found that miRNA expression is directly correlated with poorer prognosis [ 27 ].…”
Section: Direct Carcinogenesis: Ebv Infectious Cycle and Related Onco...mentioning
confidence: 99%